EVALUASI PROPERTI PSIKOMETRIS DAN PERBANDINGAN MODEL PENGUKURAN KONSTRUK SUBJECTIVE WELL-BEING - Akhtar, Hanif (Jurnal Psikologi, 2019)
In the subjective well-being (SWB) measurement model, there are three models used by researchers, namely one-factor model (unidimension), two-factors model, and three-factor model. This study aims to test the validity and reliability of the SWB measure and compare the measurement model of SWB with confirmatory factor analysis method. The total subjects used in this study were 1,003 people with an age range of 14 - 50 years. Positive Affect Negative Affect Schedule (PANAS) and Satisfaction with Life Scale (SWLS) were used as SWB measurements. The results showed all dimensions have Alpha reliability above 0.80 with item-total correlation above 0.3. The results of exploratory factor analysis showed that all items are well distributed to theirÂ  dimensions with a factor loading above 0.4. Thus the scale in this study has satisfactory validity and reliability. The comparison of three hypothetical model showed that the three-factor model has the best model fit compared to the other two models. This finding provides evidence that the three components in the SWB construct are separate and independent of each other.